Analisis Pengaruh Tingkat Suku Bunga Kredit Dan Kualitas Pelayanan Terhadap Loyalitas Nasabah Kredit (Studi kasus Nasabah Kantor Pusat Koperasi LPN Multi Usaha di Nagari Kurnia Selatan) - Hermawan, Ilham; Putri, Dini Elida; Resty, Fenisi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2024)
This research was conducted to identify and analyze and determine the influence of interest rates and service quality on credit customer loyalty (a case study of customers at the head office of the LPN Multi Usaha cooperative in Nagari Kurnia Selatan). The analytical method in this study is a quantitative method by collecting data using a questionnaire. The population in this study was 415 respondents and the sample in this study was 186, who was credit customers in Nagari Kurnia Selatan. Based on the results of research that has been done by researchers, it can be concluded that credit interest rates have a significant effect on the dependent variable, namely credit customer loyalty. In addition, there is a non-significant influence between service quality variables on credit customer loyalty. Based on the results of the F test, it was found that the credit interest rate (X1) and service quality (X2) had a significant simultaneous effect on credit customer loyalty (Y) in the Multi-Business LPN Cooperative in Nagari Kurnia Selatan.